5(m-3)+(m-4)=

Simple and best practice solution for 5(m-3)+(m-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(m-3)+(m-4)= equation:


Simplifying
5(m + -3) + (m + -4) = 0

Reorder the terms:
5(-3 + m) + (m + -4) = 0
(-3 * 5 + m * 5) + (m + -4) = 0
(-15 + 5m) + (m + -4) = 0

Reorder the terms:
-15 + 5m + (-4 + m) = 0

Remove parenthesis around (-4 + m)
-15 + 5m + -4 + m = 0

Reorder the terms:
-15 + -4 + 5m + m = 0

Combine like terms: -15 + -4 = -19
-19 + 5m + m = 0

Combine like terms: 5m + m = 6m
-19 + 6m = 0

Solving
-19 + 6m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '19' to each side of the equation.
-19 + 19 + 6m = 0 + 19

Combine like terms: -19 + 19 = 0
0 + 6m = 0 + 19
6m = 0 + 19

Combine like terms: 0 + 19 = 19
6m = 19

Divide each side by '6'.
m = 3.166666667

Simplifying
m = 3.166666667

See similar equations:

| 2c+2d+6d= | | r+240=-8r+6 | | 500/6.7=Rx6.7/6.7 | | 8x^2+20x-16=0 | | -1b+b+7-3b=2 | | 8x+5y=230 | | -29.4e-72.5=e+1356.3 | | 250000x+250000x=1000000 | | 10x-33=4x+17 | | 100x+100x=400 | | 4.1/m=2.5/34.5 | | 16.8n+4.5=n-783.92 | | 0.7=0.70 | | 8.5p+4.3=p-320.45 | | 2.4=m | | r+65.64=-0.4r+6 | | 7x+81+71=180 | | -7c+6.1=c+173.3 | | 13x+89+65=180 | | X-(7)=7 | | 2y+16=8x | | v+232.5=-7v+6.9 | | c+0.3=3.3 | | 9x-27+117=180 | | -c+6=c+67.8 | | (x-10)+2x=425 | | X-(2)=3 | | sqrt(5x+4)=8 | | 8+2r=18 | | y+103.7=-y+6.9 | | 495x+240y=600F | | 425=X+(X*2-10) |

Equations solver categories